New spring wheat mutant resources with yellow rust resistance, improved grain morphometric parameters, and high grain protein content (Eurasian Journal of Ecology, 2021)
Genetic variability in bread wheat concerning grain nutritional quality and physical morphometric parameters, which is a required prerequisite to improve modern varieties is limited. It is also important to combine the improved grain quality characteristics with tolerance to abiotic and biotic stresses including fungal disease such as yellow rust, the most common wheat disease that significantly reduces its production. The goal of present study was to broaden the genetic variation of spring bread wheat on the basis of a rust resistant cv. Kazakhstanskay-19 and mutational selection. The doses of gamma irradiation of 300 Gy, 350 Gy, and 400 Gy treatments were applied to develop new M4 mutant lines and search advanced resources which combine yellow rust resistance, improved grain morphometric parameters, and high grain protein content. The 300 Gy and 350 Gy radiation doses showed a significantly highest effect in an increase in grain area with the same level of action, showing its increased efficiency to cause mutations in the genes related to with this grain characteristics. The grain features such as length recorded significant variation only through 300 Gy treatment, indicating that only this lowest dose is effective for the improvement comparing with the higher level of radiation.Key words: genetic variation in grain nutritional quality, physical morphometric parameters, spring wheat, grain protein content.